Biventricular pacing improves clinical behavior and reduces prevalence of ventricular srrhythmia in patients with heart failure - Martinelli Filho,Martino (2002)
PURPOSE: To analyze the influence of biventricular pacing (BP) on clinical behavior, ventricular arrhythmia (VA) prevalence, and left ventricular ejection fraction (LV EF) by gated ventriculography. METHODS: Twenty-four patients with left bundle branch block (LBBB) and NYHA class III and IV underwent pacemaker implantation and were randomized either to the conventional or BP group, all receiving BP after 6 months. RESULTS: Sixteen patients were in NYHA class IV (66.6%) and 8 were in class III (33.4%). After 1-year follow-up, 14 patients were in class II (70%) and 5 were in class III (25%). Two sudden cardiac deaths occurred. A significant reduction in QRS length was found with BP (p=0.006). A significant statistical increase, from a mean of 19.13 ± 5.19% (at baseline) to 25.33 ± 5.90% (with BP) was observed in LVEF Premature ventricular contraction prevalence decreased from a mean of 10,670.00 ± 12,595.39 SD or to a mean of 3,007.00 ± 3,216.63 SD PVC/24 h with BP (p<0.05). Regarding the hospital admission rate over 1 year, we observed a significant reduction from 60. To 16 admissions with BP (p<0.05). CONCLUSION: Patients with LBBB and severe heart failure experienced, with BP, a significant NYHA class and LVEF improvement. A reduction in the hospital admission rate and VA prevalence also occurred.